Músicas, movimientos, colores en la fiesta andina. Ejemplos bolivianos - Martínez, Rosalía (2014)
In the Andean fiesta music is as much intended to be seen as it is to be heard. The multisensorial aspect of musical performance is not just a matter of the juxtaposition of sounds and sights. The analysis of the articulations that indigenous peasants of sucre (Bolivia) construct among sounds, movements and colors reveals an original organization of sensitive experience that is as much characterized by its sensory depth as it is by the ways it is linked to other domains of knowledge. The forms of culturally elaborated intersections that occur in the body of the musician lead to new perceptive configurations.